THE ASSESSMENT TOOLS FOR MEASURING HEALTHCARE WORKERS’ PREPAREDNESS FOR COVID-19 - Failenggo, Erie (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
Most countries in the world have not been prepared for COVID - 19 pandemic, so there is a need to analyze the strategies to measure our healthcare workers’ preparedness for preventing healthcare workers (HCWs) from becoming victims of COVID-19. This systematic literature review is for reviewing the various assessment tools used to measure the preparedness of healthcare workers for COVID - 19 in the time of pandemic of COVID-19 (2019 November - June 2021). During this time, we analyzed how the researchers defined and constructed the assessment tool for measuring the preparedness of healthcare workers for COVID-19. We used Scopus, Proquest, Pubmed, and Willey online library databases with search themes healthcare porkers, Preparedness, COVID-19, and assessment. Thirty-three studies measured HCWs’ preparedness for COVID-19 from November 2019 to 10 June 2021. Most studies were done in developing Nations (N=22). Almost all of the studies were Cross-sectional studies with questionnaires as their primary instrument. The definition of preparedness varied among these studies. However, all of them agreed that the tool for measuring the preparedness of HCWs for COVID-19 was constructed with more than one measurement aspect.